2007
DOI: 10.1007/s11663-007-9040-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Liquid Holdup in the Dropping Zone of a Blast Furnace—A Cold Model Study

Abstract: A two-dimensional cold model study, replicating an ironmaking blast furnace dropping zone, was carried out to estimate quantitatively the local dynamic, static, and total liquid holdups in the presence of lateral gas flow. Plastic beads were used as nonwetting packing material, and aqueous barium chloride solution was used to model the liquid flow. The X-ray visualization technique was used to image the entire packed bed followed by preliminary image processing operations in order to obtain the various types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Several researchers have pointed out that channeling of liquid flow may occur in a relatively large scale packed bed. 8,9,11) However, in the lab-scale high temperature experiments, the experimental system was not large enough to identify the channeling effect. Therefore, it is more realistic to consider the static holdup without taking into account the channeling effect.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have pointed out that channeling of liquid flow may occur in a relatively large scale packed bed. 8,9,11) However, in the lab-scale high temperature experiments, the experimental system was not large enough to identify the channeling effect. Therefore, it is more realistic to consider the static holdup without taking into account the channeling effect.…”
Section: Theorymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Shulman et al 2) suggested that the liquid holdup is composed of static and operating (dynamic) hold-up. Because of the difficulties encountered in high temperature experiments, many cold model studies have been widely carried out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10) The interaction between solid substrates such as packed beds and liquid materials have been studied by several researchers. [12][13][14][15] Among them, Jeong et al recently found out that the permeability of liquid iron in a coke bed could be enhanced by adding a new liquid material of different phase, namely, slag. In their experiments, they intentionally added both the molten iron and liquid slag into a coke bed at 1 500°C, and observed that their flows became enhanced compared with the single flow of iron and slag in the coke bed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Most of experiments have been carried out by using water models. [2][3][4] The surface tension of water is quite different from that of the liquid HCI and the slag.…”
Section: Introductionmentioning
confidence: 99%